Management of a Patient with Sudden Onset of Intra Operative Atrial Fibrillation Posted for Emergency Evacuation of Clot Following TURP Operation Under SAB - Das, Debashish; Mahmood, Wahiuddin; Ali, SM; Das, Basudeb; Khan, Ayub (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Atrial fibrillation is very common cardiac arrythmia which is encountered during the perioperative period. Atrial fibrillation in perioperative period may lead to hemodynamic impairment and thromboembolic events resulting into significant morbidity and mortality. So it is very crucial for an anesthesiologist to maintain the hemodynamic stability of the patient with atrial fibrillation and prevent furthur complications associated with it. Here we report a case of sixty year old male patient posted for emergency evacuation of clot following TURP operation. JBSA 2017; 30(1): 48-50